DAMPAK MEDIA SOSIAL TERHADAP MARAKNYA KENAKALAN REMAJA KLITIH DI YOGYAKARTA - Wila Tia Prahastiwi; Ari Prasetyoaji (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2025)
The development of technology in the current era is very related to human life. The development of technology, one of which is the development of the internet, has resulted in one of the problems, namely the use of social media for negative things, for example the klitih phenomenon in Yogyakarta. This research aims to: 1) find out why social media has an impact on the existence of klitih, 2) how social media on the rise of juvenile delinquency klitih, 3) find out what social media is used in the existence of klitih and 4) find out what efforts can prevent klitih action. This research uses a qualitative approach with the Systematic Literature Review (SLR) method. From this research, it was found that social media has an impact on the way of thinking and point of view of klitih juvenile delinquents. And social media is also used as a means of communicating with other perpetrators. Efforts that can be made to deal with this klitih problem are with parental communication patterns, school policies, living environment and policies from the authorities.